1997
DOI: 10.1093/jac/39.6.697
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of quinolone-induced small colony variants in Staphylococcus aureus

Abstract: Exposure of Staphylococcus aureus to 1 x MIC of the quinolone antibiotic pazufloxacin for 24 h, followed by plating on drug-free media, led to the emergence of small colony variants (SCVs) in addition to large colony variants (LCVs). However, following incubation with 0.25 or 4 x MIC of pazufloxacin, only LCVs were obtained. The SCVs were half as susceptible to pazufloxacin or ciprofloxacin as wild-type S. aureus, while the susceptibilities of LCVs were essentially unchanged. The reduced susceptibilities of SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 0 publications
0
10
2
Order By: Relevance
“…Because isolates in this study did not show resistance to vancomycin, it is advisable to limit the use of glycopeptides to treat only MRSA infections so as to reduce the selective pressure and likely emergence of resistance to this class of antibiotics. Decreased staphylococcal susceptibility to vancomycin is not due to transfer of vanR genes from vancomycin-resistant enterococci (VRE) or to small colony variants, as noted in staphylococci for other antimicrobial agents (Mitsuyama et al, 1997) but appears to be a gradual selection process due to treatment pressure. Glycopeptideresistant mutants of S. aureus have been experimentally selected by increasing the levels of vancomycin present during in vitro growth (Daum et al, 1992;Sieradzki and Tomasz, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Because isolates in this study did not show resistance to vancomycin, it is advisable to limit the use of glycopeptides to treat only MRSA infections so as to reduce the selective pressure and likely emergence of resistance to this class of antibiotics. Decreased staphylococcal susceptibility to vancomycin is not due to transfer of vanR genes from vancomycin-resistant enterococci (VRE) or to small colony variants, as noted in staphylococci for other antimicrobial agents (Mitsuyama et al, 1997) but appears to be a gradual selection process due to treatment pressure. Glycopeptideresistant mutants of S. aureus have been experimentally selected by increasing the levels of vancomycin present during in vitro growth (Daum et al, 1992;Sieradzki and Tomasz, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…SCVs were carefully recorded because of their undefined relevance in the selection of FQ resistance (33,35). Generally, SCVs are thought to exhibit a resistance phenotype caused by impaired heme or quinone biosynthesis (29,31). The resulting ATP deficiency, however, may also be characteristic of SCVs appearing under drug selective pressure (33).…”
Section: Discussionmentioning
confidence: 99%
“…Although SCVs have altered accumulation of drugs, including quinolones (30,37), it is difficult to envisage how changes in efflux could differentially affect drug targeting. Instead, we envisage that small-colony mutations either alter quinolone-target interactions at the level of cleavable-complex formation with gyrase and topoisomerase IV or, alternatively, influence the processing of such complexes to give the lethal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to ask whether small-colony mutants can be selected by quinolones other than NSFQ-105 and sparfloxacin and acquire further mutational resistance. It has been reported that small-colony mutants are induced in liquid culture at the MIC by pazufloxacin, a putative dual-target agent (42), and by nalidixic acid, which is thought to target gyrase, but not by ciprofloxacin, norfloxacin, fleroxacin, enoxacin, pipemidic acid, or tosufloxacin, which act through topoisomerase IV (30). More work will be needed to establish whether failure to recover small-colony mutants in vitro is due to a chemical feature of the quinolone or, more likely, a narrow selection window given their low-level (twofold) resistance.…”
Section: Discussionmentioning
confidence: 99%